2015
DOI: 10.2463/mrms.2014-0077
|View full text |Cite
|
Sign up to set email alerts
|

Intersite Reliability of Diffusion Tensor Imaging on Two 3T Scanners

Abstract: We report the intersite scan reliability of diffusion tensor imaging (DTI) parameters using identical 3T scanners and acquisition protocols at 2 sites. Voxel-based analysis revealed several regions with significant intersite differences. The intersite reliability of DTI measures showed coefficients of variation below 4% in tract-specific analysis (TSA) and below 6% in atlas-based analysis. Given the excellent reliability of TSA, our results suggest it as a promising and useful tool for multicenter DTI studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…Fox et al ( 12 ) reported inter-vendor and inter-session CV of FA as 6.8–9.1%. In contrast, other studies reported ranges of CV of FA as 1–3% ( 13 ) and less than 4% ( 10 ). Our results are more consistent with the latter studies, suggesting that FA exhibits good reliability.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Fox et al ( 12 ) reported inter-vendor and inter-session CV of FA as 6.8–9.1%. In contrast, other studies reported ranges of CV of FA as 1–3% ( 13 ) and less than 4% ( 10 ). Our results are more consistent with the latter studies, suggesting that FA exhibits good reliability.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies have reported the reproducibility of DTI over time using one or more scanners from the same vendor and demonstrated acceptable agreement ( 8 10 ). Other studies have examined the inter-vendor reliability of DTI but reported conflicting results ( 4 6 8 11 12 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study, Kamagata et al 17 scanned 7 volunteers at two sites, both using 3T Philips Achieva scanners. By using several analytical methods, including voxel-wise comparison with TBSS, atlas-based analysis, and tract specific analysis, they reported CoV inter-site variability <4% in the case of tract-specific analysis, and a CoV <6% by using the atlas-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…multi-center study). 6 , 7 QC itself is widely performed in daily clinics, but standard water phantoms for such general checks are not optimal for DTI validation because they do not contain diffusional anisotropy. Therefore, special DTI-QC phantoms that have an appropriate diffusional anisotropy are needed.…”
Section: Introductionmentioning
confidence: 99%